EXAMINING THE CHARACTERISTICS OF EFFECTIVE CO-OPERATIVE LEADERSHIP: INSIGHTS FROM COMMITMENT, VISION, AND BUSINESS ACUMEN IN MALAYSIA - Muhammad Fadzly Zakaria; Nurul Syazwani Ahmad Sabri; Siti Noorjannah Abd Halim; Nur Yuhainis Ab Wahab (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This paper investigates valuable and relevant factors that will improve co-operative leadership in Malaysia with a focus on a collective drive, social responsibility, and sound business judgment. A qualitative research design was employed, and the data was collected from Malaysian co-operative leaders. The participants are chosen from among co-operative leaders in Malaysia, such as board members and executive officers. The objective of the study is to identify practical strategies that can boost the resiliency of co-operative societies and enhance their community engagements. The concept of a shared vision is understood as a unifying factor, community commitment is important in ensuring that social value is created, while business savvy is seen as critical for competition in the marketplace. It is anticipated that this research will identify the interaction among the three attributes, and how they together are conducive to the achievement of sustainable co-operative leadership, from the viewpoint s of the stakeholders who wish to see the development of Malaysian co-operatives’ sector.